Quantifying the Increase in Radiation Exposure Associated with SPECT/CT Compared to SPECT Alone for Routine Nuclear Medicine Examinations. (4th July 2011) - Larkin, Ann M.; Serulle, Yafell; Wagner, Steven; Noz, Marilyn E.; Friedman, Kent
Abstract : Purpose . We quantify the additional radiation exposure in terms of effective dose incurred by patients in the CT portion of SPECT/CT examinations. Methods . The effective dose from a variety of common nuclear medicine procedures is calculated and summarized. The extra exposure from the CT portion of the examination is summarized by examination and body part. Two hundred forty-eight scans from 221 patients are included in this study. The effective dose from the CT examination is also compared to average background radiation. Results . We found that the extra effective dose is not sufficient to cause deterministic effects. However, the stochastic effects may be significant, especially in patients undergoing numerous follow-up studies. The cumulative effect might increase the radiation exposure compared to patient management with SPECT alone. Conclusions . While the relative increase in radiation exposure associated with SPECT/CT is generally considered acceptable when compared with the benefits to the patient, physicians should make every effort to minimize this effect by using proper technical procedures and educating patients about the exposure they will receive.